Uso del tensiometro en la determinación del régimen de riego en el cultivo de frejol phaseolus vulgaris l bajo invernadero - Lapo Romero, Luis Alberto (2018)
Irrigation programming based on the real-time measurement of soil water status through tensions according to a specific crop has been recognized as a promising approach for the efficient management of irrigation in greenhouses. The identification of appropriate irrigation reference points is crucial for optimum crop yield, both in terms of yield and quality based on the control of matrix potential over growth and plant-water relationships. The objective of the present study was to determine the irrigation regime by using the tesiometer in the bean crop by means of 10 cb, 20 cb and 30 cb voltages calculating the biomass to determine physiologically which tension is the best for the crop and to carry out an analysis of linear regression to determine if there is correlation in the sheets applied by the different tensions with the crop evapotranspiration. The work was carried out in the greenhouse of the Santa Ines farm of the Agricultural Sciences Academic Unit whose climate and ecology represent a subhumid water index with a large deficit in the dry season whose thermal regime is warm and the climate is tropical dry megatérmico with an area of very dry tropical forest life and an average annual temperature of 25 ° C. A randomized block design with three treatments and three repetitions at different voltages was used. Within the statistical test, a simple variance analysis was carried out whose factor was the tension which were subjected to the treatments where the null hypothesis was rejected in the biometric variables of the plants, performing a multiple range analysis by means of Tukey at 95% reliability. The results show a high statistical difference between the treatments of 10 and 20 cb, with respect to the biometric variables of weight, green matter, dry matter and number of grains per plant. On the other hand, treatment 1 in which the soil was subjected to a tension of 10 cb, the highest weight of green matter was obtained with 195.19 grams per plant, more weight was obtained per seed compared to treatment 2 with 15.04 grams per plant, treatment 3 obtained the lowest value of these biometric variables, most of the data presented a normal distribution where asymmetry and kurtosis were kept within the appropriate ranges that determine their behavior, as for the sheets applied in treatment 1, we presented the highest sheets of 260.59 mm with 10 cb, 226.64 mm with 20 cb, 206.02 mm the treatment 3 and 237.80 mm in the ETc. In the linear regression analysis carried out between the applied sheets of the stresses with the ETc, a significant and acceptable correlation with the treatments could be observed. The study of tensiometers was in accordance with the evapotranspiration readings, since it is recommended to carry out a study in which vegetable production based on evapotranspiration with the tensions present in the soil is taken as a treatment.